NILAI PENDIDIKAN KARAKTER DALAM CERITA RAKYAT KABUPATEN BANTUL â€œKI AGENG MANGIRâ€ (KAJIAN FOLKLOR) - Himawan, Riswanda Riswan (Universitas Ahmad Dahlan, 2020)
The problem in this study is how the structure of the folklore